Comparison of effects of intravenous clonidine and dexmedetomidine for blunting pressor response during laryngoscopy and tracheal intubation: A randomized control study - Sarkar, Arindam (Anesth Essays Res, 2014)
CONTEXT: Laryngoscopy and endotracheal intubation activates the sympathetic nervous system, causing tachycardia and hypertension. Dexmedetomidine has an affinity for alpha(2) receptors 8 times greater than that of clonidine. It diminishes norepinephrine release and inhibits sympathetic activity leading to decreased heart rate (HR) and blood pressure. AIMS: The aim was to compare the effect of intravenous (IV) infusion of dexmedetomidine and clonidine on the pressor response among patients undergoing tracheal intubation in elective surgeries under general anesthesia. SETTINGS AND DESIGN: A prospective, randomized control study. SUBJECTS AND METHODS: Seventy-five adult patients of age 18-55 years in American Society of Anesthesiologists physical status I and II were included in this study. Patients were allocated randomly into Group P, Group D and Group C of 25 patients each. In the operation theatre, clonidine (3 μg/kg) or dexmedetomidine (0.5 μg/kg) or placebo (0.9% normal saline) diluted in 100 ml NaCl 0.9% were infused over a period of 10 min. STATISTICAL ANALYSIS USED: Statistical analysis was done using Statistical Package for Social Sciences version 15.0. Chi-square test, ANOVA, Student's t-test, and Paired t-test were used. RESULTS: As compared to Group P, the mean systolic blood pressure in Group D and Group C were significantly lower (<0.01) after intubation and all the subsequent intervals. After infusion and after the induction interval, the maximum value was observed in Group D while minimum mean value was observed in Group C. As compared to Group P, the mean arterial pressure in Group D was significantly higher at after infusion and after induction intervals but significantly lower after intubation and subsequent intervals. However, in Group C, the mean value was significantly lower as compared to Group P at all-time intervals except after infusion and after induction intervals. As compared to Group P, the mean HR in Group D was significantly higher at after infusion and after induction intervals. However at all the subsequent intervals, Group D was significantly lower as compared to Group P. CONCLUSION: It was found that attenuating response to hemodynamic changes were observed with dexmedetomidine and clonidine IV infusion. The early onset of dexmedetomidine makes it a promising choice. Hence premedication with IV infusion of dexmedetomidine can safely be recommended for attenuation of hemodynamic response to endotracheal intubation.